Jam on : the craft of canning fruit - McCarthy, Laena (Viking Studio, 2012)
In Jam On, New York's "Jam Queen" Laena McCarthy shares her love of making inventive handmade jam with delicious recipes and canning techniques. Her down-to-earth approach and unique, easy method allows even the novice cook to make fresh and exciting jam. The recipes in Jam On use less sugar, making the jams not only healthier, but more intensely flavorful than your average fruit concoction. With step-by-step instructions and four-color photographs throughout, McCarthy guides readers through the canning process and offers inventive herb and spice combinations for a range of signature jams--